ANALYSIS OF VILLAGE PLANNING, BUDGETING, AND DEVELOPMENT IN CISIMEUT RAYA VILLAGE LEUWIDAMAR LEBAK - Bambang Setyo Panulisan; Wiwien Susanti; Ahmad Sudadi; Ajeng Liyan Putikasari (Nindikayla Institute, 2023)
The results of preliminary research on the use of a medical website of a hospital showed a usability value of 2.3 out of a scale of 4, which means that the quality of the website's services is not satisfactory, so patients are reluctant to use medical portal services. Even though the hospital patient service portal is an essential medium after the Covid-19 pandemic, it can be used to increase pasiesn access to hospitals by not knowing the time. The non-stop operation of the portal can help patients get the information and services that patients need anytime and anywhere. . However, not all services can satisfy customers or patients. The behavior of the people of the